Transpupillary collagen photocrosslinking for targeted modulation of ocular biomechanics. (April 2021) - Gerberich, B.G.; Hannon, B.G.; Hejri, A.; Winger, E.J.; Schrader Echeverri, E.; Nichols, L.M.; Gersch, H.G.; MacLeod, N.A.; Gupta, S.; Read, A.T.; Ritch, M.D.; Sridhar, S.; et al.
Abstract: The central vision-threatening event in glaucoma is dysfunction and loss of retinal ganglion cells (RGCs), thought to be promoted by local tissue deformations. Here, we sought to reduce tissue deformation near the optic nerve head by selectively stiffening the peripapillary sclera, i.e. the scleral region immediately adjacent to the optic nerve head. Previous scleral stiffening studies to treat glaucoma or myopia have used either pan-scleral stiffening (not regionally selective) or regionally selective stiffening with limited access to the posterior globe. We present a method for selectively stiffening the peripapillary sclera using a transpupillary annular light beam to activate methylene blue administered by retrobulbar injection. Unlike prior approaches to photocrosslinking in the eye, this approach avoids the damaging effects of ultraviolet light by employing red light. This targeted photocrosslinking approach successfully stiffened the peripapillary sclera at 6 weeks post-treatment, as measured by whole globe inflation testing. Specifically, strain was reduced by 47% when comparing treated vs. untreated sclera within the same eye (n = 7, p=0.0064 ) and by 54% when comparing the peripapillary sclera of treated vs. untreated eyes (n = 7, p<0.0001 ). Post-treatment characterization of RGCs (optic nerve axon counts/density, and grading), retinal function (electroretinography), and retinal histology revealed that photocrosslinking was associated with some ocular toxicity. We conclude that a transpupillary photocrosslinking approach enables selective scleral stiffening targeted to the peripapillary region that may be useful in future treatments of glaucoma. Graphical abstract: Image 1 Highlights: Localized stiffening of the posterior eye may be a treatment strategy for glaucoma and myopia. We sought to photocrosslink scleral collagen, using methylene blue as a photoinitiator, in vivo . We stiffened an annular region around the optic nerve with a transpupillary red light beam. Moderate treatment toxicity was identified using axon counts, histology, and electroretinography.